Analisis manfaat ekologis spesies dominan di RTH Kota Samarinda menggunakan national tree benefit calculator - Putri, Dina Hayati; Budiman, Budiman (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2026)
Urban Green Space (UGS) plays a crucial role in maintaining ecological balance and enhancing the quality of urban environments. This study aims to identify species and analyze the ecological benefits of dominant species in the UGS of Samarinda City using the National Tree Benefit Calculator (NTBC). The research method involved identifying the types and numbers of dominant species in several city parks, then calculating ecological benefits, such as vegetation's ability to reduce pollutants. The results show that the dominance of large trees in Samarinda City's UGS is a positive indicator that the UGS has been well-managed and provides significant ecological, social, and aesthetic benefits. Research suggests that Polyalthia longifolia absorbs the highest amount of pollutants, including carbonmonoxide (2,65 oz), ozone (10,46 oz), nitrogen dioxide (126,1 oz), sulphur dioxide (22,57 oz), and PM2.5 (6,58 oz). This study recommends selecting appropriate species for UGS development, with ecological benefits in mind. The findings are expected to serve as a reference for policymakers in planning and managing sustainable UGS in Samarinda City.